Effectiveness Of Kaltenborn Mobilization Versus Muscle Energy Technique On Shoulder Range Of Motion In Adhesive Capsulitis - Umar, Muhammad; Anwar, Aqsa; Khan, Nida; Marryam, Misbah; Rashid, Hiba (Journal of Rawalpindi Medical College, 2023)
Objective: To compare the effectiveness of muscle energy techniques (post isometrics relaxation) and Kaltenborn mobilizations on shoulder range of motion (ROM) in adhesive capsulitis. Methodology: A randomized Control Trial (CRT) was conducted on patients with adhesive capsulitis for 6 months September 2021 to February 2022. Data was collected through a convenient sampling technique. 30 patients were taken from the physiotherapy department of the holy family hospital, Rawalpindi. The sample size was calculated using the Open Epi Tool. Data was collected by using Universal Goniometer at baseline, after 2 weeks and after 4 weeks of treatment. Patients who met the inclusion criteria and gave consent were included in the study. Patients were randomly allocated into two groups: Group A & Group B. Group A received muscle energy technique and Group B received grade II & III Kaltenborn mobilizations. Results: Data was analysed using SPSS software version 22. Both groups showed improvements in shoulder range of motion but Group A showed a statistically significant difference (p<0.05) in flexion and abduction ROM from Group B. Conclusion: The muscle energy technique is much more effective in improving flexion and abduction ROM except rotation than Kaltenborn mobilizations in adhesive capsulitis.